SOCIAL SKILL TRAINING (SST) UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP X DI KABUPATEN PRINGSEWU - Fixi Intansari (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2023)
The purpose of this community service activity is to equip students to be more confident in communicating effectively, and to have the courage to express themselves in a new social environment. Social Skill Training (SST) for SMP GR students was held on Saturday, 24 June 2023 in one of the classrooms of SMP X, Pringswu district. Community service activities in the form of training are given using the off the job method, namely training that uses situations outside of learning. In general, the steps for Community Service activities can be divided into three stages, namely preparation (observation), implementation (intervention), and evaluation. Based on the results of the intervention, almost 70% of students were able to carry out social interactions to make lots of friends. while the rest still find it difficult to expand their social circle because they feel shy and lack confidence. Most of the participants also said that they were happy when they were in a new environment, because then they had the opportunity to introduce themselves and make friends with new people. Even so, some participants also felt that they still had difficulty communicating with other people. The biggest difficulty experienced by some participants was related to their lack of language skills (word mastery). To overcome these problems, students also revealed that they dared to ask for help from others when they were in trouble. They seek help from parents, teachers or familiar friends.